DIAGNÓSTICO DE LAS CONDICIONES DE SEGURIDAD Y SALUD EN EL TRABAJO EN EL SECTOR TURISMO DURANTE EL COVID 19. GUACHETÁ - CUNDINAMARCA - Erika Peña; Mery Melo; Ana Carrillo; Gina Fuentes (Revista Ingeniería, Matemáticas y Ciencias de la Información)
According to the World Tourism Organization (UNWTO), tourism is defined as a social, cultural and economicphenomenon, in which a movement of people between countries or in the same place of residence is generated,occasionally due to personal, work or professional aspects. The present investigation is of an observational type, cross-sectional, quantitative approach, and descriptive scope. A data collection instrument was designed with sociodemographicand occupational variables, health conditions, and occupational health and safety conditions. The results allow us toobserve that of the total population only 25% have a contributory health regime, 16.7% have affiliation to the occupationalrisk insurer, there is a lack of knowledge about biosafety measures. identification of hazards and risks in their workplaces,and a negative impact due to the COVID 19 pandemic. Additionally, biological, chemical, ergonomic and psychosocialrisks are identified, for which it is necessary to carry out a mapping of the companies in order to be able to implement theprotocols, processes and procedures that guarantee the safety and health of visitors and tourists.